Meeting Room Reservation Mobile Base System for PT. Visionet Data Internasional - Ade Setiadi; Fifit Alfiah; Fajar Septiawan (Universitas Raharja, 2020)
Reservation Meeting Room System is a system that is used to reserve meeting rooms in real time in all offices of PT. Visionet Data Internasional, so that this system is easy for employees to use, there is no duplication of reservations for meeting rooms between employees, and can be used through employees' mobile devices. PT Visionet Data Internasional is a company engaged in the field of IT Consultants consisting of many departments that focus on the development and maintenance of software and hardware, with many departments using meeting rooms very intensely, obtained information systems used to book meeting rooms are inaccurate, not real time, complicated, and frequent duplication of orders. Therefore the system that will be created by the author is a renovation and update of the previous system that already exists at PT. Visionet Data Internasional. It is expected that with this system, it can minimize errors that occur in the previous system. This system is also expected to make it easier for all employees to book a meeting room at PT Visionet Data Internasional.